Logan Rees: capstone - Rees, Logan, artist (Colorado State University. Libraries, 2022)
The artist's statement: My work represents something that I believe is a natural human tenant, something that is ingrained in almost all people, and that is the want to create. Things I create cover a range of materials, from the physical to the digital. This includes acrylic murals and paintings, workshop sculpture, fibers weaving, metal sculptures, and digital art. My process of making is sporadic, ranging from periods of quick bursts of large-scale works to long periods of hyper-focused detail work. It all depends on my mood and the artwork that is being created. There is always a brief planning stage, although I do not like to stay here for too long. I like to have a rough guide and then figure out details as I fit everything together. From there, it is a matter of working on everything involved in the piece at the same time and bringing it together at the end. What inspires me is my drive to create something ‘more’. What this means varies from project to project and is not even a specific thing, but it keeps me moving forward. Sometimes I am struck by an idea to take my first idea further than the original parameters, and I must make this vision happen. Sometimes I come to an idea that is just at the edge of my ability and will skate that edge of frustration to test myself. It is a fun and productive way of learning new skills. I have no concrete inspiration for my work, just a driving force and need to create. That said, as of late a lot of my work has dealt in some way with duality. I recently made a pendant that spins on an axis around a fixed stone, with two different sides that point to duality and decision making. I finished a fiber weaving set that had a sturdily built towel that would face wear, paired with a loosely made wall-mounted piece to show a different duality. Due to their inherent power, pair and opposites are always a good source to draw from.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design